Heidegger: lo strappo nell’arte - Curcio, Nicola (Scenari, 2021)
From Heidegger’s writings on art, and specially from the principal essay in the 30’s, The Origin of the Work of Art, we can earn some tools for the comprehension of certain artistic expressions, which can in their turn illuminate the philosopher’s writing, for example some canvas works by Lucio Fontana. Giving up the fundamental ontology of Being and Time Heidegger assumes a circular pattern derived from his development of the Kehre-thought: just as in this thinking the Da-sein can relate to the Being in its holding on its own (epochè), in the same way the work of art produces an empathy, in which the world-building spectator accesses to the closure of the thingness of the artefact. In this sense the “strife of earth and world” reflects the ontology of the Kehre. And the essential art gesture, named Riß (drawing), is the place par excellence of the unconcealment, in which truth is fixed in figure.